Minimizing the Electrolyte Volume in Li–S Batteries: A Step Forward to High Gravimetric Energy Density. Issue 26 (6th August 2018) - Agostini, Marco; Hwang, Jang‐Yeon; Kim, Hee Min; Bruni, Pantaleone; Brutti, Sergio; Croce, Fausto; Matic, Aleksandar; Sun, Yang‐Kook
Abstract: Sulfur electrodes confined in an inert carbon matrix show practical limitations and concerns related to low cathode density. As a result, these electrodes require a large amount of electrolyte, normally three times more than the volume used in commercial Li‐ion batteries. Herein, a high‐energy and high‐performance lithium–sulfur battery concept, designed to achieve high practical capacity with minimum volume of electrolyte is proposed. It is based on deposition of polysulfide species on a self‐standing and highly conductive carbon nanofiber network, thus eliminating the need for a binder and current collector, resulting in high active material loading. The fiber network has a functionalized surface with the presence of polar oxygen groups, with the aim to prevent polysulfide migration to the lithium anode during the electrochemical process, by the formation of S–O species. Owing to the high sulfur loading (6 mg cm −2 ) and a reduced free volume of the sulfide/fiber electrode, the Li–S cell is designed to work with as little as 10 µL cm −2 of electrolyte. With this design the cell has a high energy density of 450 Wh kg −1, a lifetime of more than 400 cycles, and the possibility of low cost, by use of abundant and eco‐friendly materials. Abstract : Lithium‐Sulfur batteries are designed using free‐standing nanofiber networks functionalized at the surface by oxygen polar groups. Thanks to the removal of the current collector, conductive agents and binders, and the reduction in electrolyte volume the battery achieves a practical energy of 450 Wh kg ‐1 with a lifetime of 400 cycles and the possibility of low cost, by the use of abundant and eco‐friendly materials.